Gaya Komunikasi Kesehatan Untuk Penyembuhan Depresi Akibat Perundungan: (Analisis Semiotika Roland Barthes Pada Video YouTube @aymanalatas) - Ramdani, Taufik; Maulida, Sindi Dewanti; Rahman, Mufti Fauzi; Ameliana, Latifa; Wahidah, Alisya Fitriya Nur; Saputra, Deni (DAS Institute, 2025)
In the current era, information can be easily spread widely, this is due to advances in information technology, namely new media. This study analyzes the communication style in accordance with the Communicator Style Measure (CSM) theory, on a a doctor in a YouTube video that discusses bullying and depression. The method used is Roland Barthes' semiotic analysis, which is a method to find out the denotative and connotative signs in a video show. The purpose of this study is to find out the communication style used by a doctor in a video that educates about depression caused by bullying. The results indicate that at the denotation level, bullying is not only physical violence but also verbal, such as teasing that is often taken as a joke. At the connotation level, the term